Changes in forest nitrogen cycling across deposition gradient revealed by δ15N in tree rings - Oulehle, Filip; Tahovská, Karolina; Ač, Alexandr; Kolář, Tomáš; Rybníček, Michal; Čermák, Petr; Štěpánek, Petr; Trnka, Miroslav; Urban, Otmar; Hruška, Jakub (Environmental pollution (Barking, Essex, 2022)
Tree rings provide valuable insight into past environmental changes. This study aimed to evaluate perturbations in tree ring width (TRW) and δ15N alongside soil acidity and nutrient availability gradients caused by the contrasting legacy of air pollution (nitrogen [N] and sulphur [S] deposition) and tree species (European beech, Silver fir and Norway spruce). We found consistent declines of tree ring δ15N, which were temporarily unrelated to the changes in the TRW. The rate of δ15N change in tree rings was related to the contemporary foliar carbon (C) to phosphorus (P) ratio. This observation suggested that the long-term accumulation of 15N depleted N in tree rings, likely mediated by retained N from deposition, was restricted primarily to stands with currently higher P availability. The shifts observed in tree-ring δ15N and TRW suggest that acidic air pollution rather than changes in stand productivity determined alteration of N and C cycles. Stable N isotopes in tree rings provided helpful information on the trajectory of the N cycle over the last century with direct consequences for a better understanding of future interactions among N, P and C cycles in terrestrial ecosystems.
Keywords: Carbon Isotopes; Picea; Nitrogen; dusík; Forests; Ecosystem; Isotope; lesy; Nitrogen Isotopes; Tree species; Phosphorus; Eutrophication; buk (rod); izotopy dusíku; izotopy uhlíku; smrk; Forest productivity; Fagus; nitrogen; ekosystém